2015
DOI: 10.1080/00207543.2015.1059521
|View full text |Cite
|
Sign up to set email alerts
|

How big data and analytics reshape the wearable device market – the context of e-health

Abstract: The wearable device can be a key link between health care and big data and analytics (BDA). The benefits of BDA in health care have been widely acknowledged, but the uncertainty of the implementation of BDA has led some firms to hesitate in adopting this technology. In this research, we are keen to answer the key questions of whether the wearable device firms would adopt the BDA strategy, and how much effort they would put into it. We propose a competition model between the wearable device firms with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…They introduced the concepts of 'group signature' and 'authority'. Wu et al (2017) considered consumers' preference to big data analytics in their model of competition between wearable device companies with and without adopting big data analytics. They found that when the consumers have different preferences, the market structure impacts the competition.…”
Section: Customer Managementmentioning
confidence: 99%
“…They introduced the concepts of 'group signature' and 'authority'. Wu et al (2017) considered consumers' preference to big data analytics in their model of competition between wearable device companies with and without adopting big data analytics. They found that when the consumers have different preferences, the market structure impacts the competition.…”
Section: Customer Managementmentioning
confidence: 99%
“…In terms of detection, Na et al developed a hearing aid dynamic electromechanical device [ 16 ]; in terms of surgical navigation, Rosenthal and Harmsen designed a visual navigation software for cancer tumor resection [ 17 19 ]. It can be seen that wearable device applications have many advantages in the medical and health industry, and researchers are turning theory into a real product, and the medical health industry can be expected to be an important market for wearable devices in the future [ 20 , 21 ]. According to ABI Research, a US research and analysis company, the revenue of wearable wireless medical health equipment is expected to exceed $8 billion in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The classical Hotelling classical model is used to represent consumer preferences in response to horizontal product differentiation based on spatial locations (Daspremont, Gabszewicz, & Thisse, 1979; Hotelling, 1929; Wu, Li, Lin, & Goh, 2017; Yao & Zhang, 2012). In our study, patients have the access to services offered by traditional medical outlets and competitive service provided by online medical platforms and can make their choice with the help of healthcare information technologies.…”
Section: Methodsmentioning
confidence: 99%